PENETAPAN HARGA JUAL ES BALOK PADA PT. ES MUDA PERKASA DENGAN MENGGUNAKAN METODE TARGET PROFIT PRICING - Amni, Chairul (Department of Accounting, Faculty of Economics & Business, 2019)
Company pricing must be very careful so that the price offered is not too expensive or cheap but still produces more profits for the company, but this becomes a weakness for the company if competitors are able to provide lower prices. PT. Es Muda Perkasa has a selling price that is considered sufficient to compete in the industrial world but the prices offered by PT. Es Muda Perkasa allegedly still low. It is certainly difficult for companies to be able to compete because the price determination applied is only based on estimates, so the prices set are not in accordance with production costs. Therefore the company needs to review the way of pricing strategies so that the benefits can be maximized. This study aims to determine the price of selling ice blocks by using profit pricing targets to get profits according to their production costs. The research method used in this study is to use a profit pricing target method that uses break-even analysis, where the company will not get profits and shortages of capital that has been spent. Data collection using the approach of observation, interviews, and literature study. The results of the study show that the price set by the company is still low at Rp. 16000; / stem compared to the price made by the Target Profit Pricing method which is the product cost of Rp. 18.496412 / stem assuming a profit of Rp.20,551 / stem for a profit of 10%, then Rp.21,760 / stem for a profit of 15% and Rp.23,120 / stem for a profit of 20%